PENGELUARAN KONSUMSI MASYARAKAT: DARI TEORI SAMPAI DENGAN EMPIRIS - Purwaningsih, Yunastiti (Universitas Muhammdaiyah Surakarta, 2001)
The household behavior in deciding consumption expense and revenue which will be saved is individual decision in microeconomic scope, but this behavior aggregately contains macroeconomic consequence. Household consumption decisions influence on the whole behaviors, either in long or short term.This writing is a study on consumption expense from theoretical to empirical point of view. The discussion is begun with consumption theories, influencing factors, and research results or consumption data as empirical discussion.